Harnessing ambient sound: Different approaches to acoustic energy harvesting using triboelectric nanogenerators - Fandi Jean; Muhammad Umair Khan; Anas Alazzam; Baker Mohammad (Journal of Science: Advanced Materials and Devices)
As a sustainable energy source, sound is abundant in the environment, but its effective conversion into electrical energy remains a technical challenge. Triboelectric nanogenerators (TENGs) have made significant progress in addressing this issue, enabling the efficient capture of low-frequency sound waves and their transformation into usable power. This review explores the core principles behind acoustic energy harvesting using TENGs and examines key advancements in materials and resonator designs, including Helmholtz and quarter-wavelength configurations, which enhance energy conversion. Recent breakthroughs in TENG technologies are also highlighted, focusing on specialized mechanisms and innovative structural designs that improve sound wave collection and energy transfer. The review also looks into the various applications of TENGs, including harnessing urban noise, enhancing voice recognition systems, and powering wearable devices. Finally, challenges and future directions for expanding the use of acoustic energy harvesting technologies are discussed,focusing on their potential to provide practical and scalable energy solutions for various applications.